2011
DOI: 10.1038/ki.2010.430
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and calcium nephrolithiasis

Abstract: Calcium nephrolithiasis is one of the most prevalent uronephrologic disorders in the western countries. Studies in families and twins evidenced a genetic predisposition to calcium nephrolithiasis. Family-based or case-control studies of single-candidate genes evidenced the possible involvement of calcium-sensing receptor (CASR), vitamin D receptor (VDR), and osteopontin (OPN) gene polymorphisms in stone formation. The only high-throughput genome-wide association study identified claudin 14 (CLDN14) gene as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 58 publications
2
48
0
4
Order By: Relevance
“…If distal renal tubular acidosis (dRTA) is identified, 28,29 an underlying cause should be sought. Calcium phosphate stones are a feature of many rare monogenic diseases 30 including inherited forms of dRTA and the X-linked condition, Dent's disease.…”
Section: Calcium Phosphate Stonesmentioning
confidence: 99%
“…If distal renal tubular acidosis (dRTA) is identified, 28,29 an underlying cause should be sought. Calcium phosphate stones are a feature of many rare monogenic diseases 30 including inherited forms of dRTA and the X-linked condition, Dent's disease.…”
Section: Calcium Phosphate Stonesmentioning
confidence: 99%
“…Albumin, for example, may play a role as an inhibitor to decrease stone formation 2 . However, some urinary proteins may also promote stone formation 3 . Recently, we isolated albumin from calcium oxalate (CaOx) stones and found that albumin can induce CaOx nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture down-regulated the genes involved in muscle breakdown (atrogin-1 and muscle RING-finger protein-1) and upregulated Akt1 and Transient receptor potential cation channel subfamily V member 4, which are positive regulators of protein synthesis. In another study, Takaoka et al 6 demonstrated that electroacupuncture treatment induced satellite cell proliferation in nonatrophic skeletal muscle through the suppression of myostatin expression.…”
mentioning
confidence: 99%
“…6 The study by Halbritter et al in this issue of JASN is therefore welcome in suggesting that perhaps a larger proportion of symptomatic stones are in fact the result of known, single-gene disorders. 7 The study did not, by intent, attempt to reveal new genetic contributors to kidney stones.…”
mentioning
confidence: 99%